2012
DOI: 10.1097/meg.0b013e328355638f
|View full text |Cite
|
Sign up to set email alerts
|

The management of cyclic vomiting syndrome

Abstract: Cyclic vomiting syndrome (CVS) is a rare abnormality of the neuroendocrine system that affects 2% of children. It is a frequently missed diagnosis in the emergency department and may require a number of emergency department visits before the diagnosis is made. The objectives of this review are to identify the clinical features that suggest a diagnosis of CVS and to review the literature on its management. The MEDLINE and EMBASE databases were searched from January 1948 to October 2011 using the keywords 'Cycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 35 publications
4
67
0
1
Order By: Relevance
“…In our small case series, 6 of 14 patients achieved full remission with amitriptyline, and a further 2 showed a substantial improvement in symptoms. The findings are in keeping with a meta-analysis of previous studies,12 and thus support the use of TCADs as an efficacious prophylactic treatment option for CVS.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In our small case series, 6 of 14 patients achieved full remission with amitriptyline, and a further 2 showed a substantial improvement in symptoms. The findings are in keeping with a meta-analysis of previous studies,12 and thus support the use of TCADs as an efficacious prophylactic treatment option for CVS.…”
Section: Discussionsupporting
confidence: 88%
“…A recent systematic review and meta-analysis of 25 separate cohorts of patients with CVS reported a higher proportion of patients with headaches or migraines (40%) than seen in our case series 12. There was also a family history of headaches or migraines in 40% in this meta-analysis.…”
Section: Case Seriessupporting
confidence: 42%
See 1 more Smart Citation
“…Prophylaxis with tricyclic antidepressants in the asymptomatic phase has been shown to be helpful in 75.5% of adult patients and 67.6% of pediatric patients, in a non-placebo-controlled cohort study. 15 Propranolol has also been shown to be effective as prophylactic treatment in children. 16 Patients presenting with symptoms of CVS often undergo extensive evaluation for alternative causes of their symptoms.…”
Section: Cvsmentioning
confidence: 99%
“…The patient could be discharged 4 h later and was counseled to stop smoking marijuana [118]. Propranolol is a nonspecific, lipophilic beta-1/beta-2-blocker that has been used to treat CVS, particularly in pediatric patients [119]. Its use in CHS has to date been very limited.…”
Section: Treatmentmentioning
confidence: 99%